2012
DOI: 10.21091/mppa.2012.4039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Playing-Related Musculoskeletal Disorders in Traditional Korean String Instrument Players

Abstract: This study was performed to investigate the prevalence of musculoskeletal disorders in players of a variety of traditional Korean classical instruments: gayageum, geomungo, ajaeng, and haegeum. A large percentage of these musicians suffer from musculoskeletal pain of various body parts. However, there has been no research regarding the extent of musculoskeletal disorders in players of these instruments. Through a focus group interview, a questionnaire was developed to investigate musculoskeletal disorders. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Some 22 studies also investigated the association between different MSS outcomes. Similar to the extent/severity studies, the majority (86%) of the studies of risk factors reported general symptom outcomes[27,28,30,38,[40][41][42][43][44][45][46][47][48][49][50]53,54,60,64,65,69,71,74,76,[79][80][81][82][83][84][85][86][87][88][91][92][93][95][96][97][106][107][108]110,111,115,116,119,122,125,126,[129][130][131][133][134][135][138][139][140][141][142][154][155]…”
mentioning
confidence: 99%
“…Some 22 studies also investigated the association between different MSS outcomes. Similar to the extent/severity studies, the majority (86%) of the studies of risk factors reported general symptom outcomes[27,28,30,38,[40][41][42][43][44][45][46][47][48][49][50]53,54,60,64,65,69,71,74,76,[79][80][81][82][83][84][85][86][87][88][91][92][93][95][96][97][106][107][108]110,111,115,116,119,122,125,126,[129][130][131][133][134][135][138][139][140][141][142][154][155]…”
mentioning
confidence: 99%
“…CINAHL: Cumulative Index to the Nursing and Allied Health Literature; MSS: Musculoskeletal symptoms.). Of these articles, there were 110 unique studies, with some articles reporting on the same dataset27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50 ) . Values reported throughout this review refer to the 110 unique studies, unless otherwise indicated.…”
Section: Resultsmentioning
confidence: 99%
“…To guide the collection of data for specific body regions, 14 studies reported using a body chart27,28,29,30, 33, 35, 38, 39, 43,44,45,46, 56, 66, 68, 74, 80, 89, 131, 138 ) ; six studies including the body chart within the article33, 80, 89 ) , or the questionnaire in the appendix39, 131, 138 ) . While 11 studies did not specifically report that a body chart was used31, 32, 34, 36, 37, 57,58,59,60, 72, 116, 118, 124 ) , they reported using questionnaires that include body charts30, 33, 51, 64, 71, 114, 117, 123 ) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations